Pembuatan Papan Partikel Berukuran Komersial dari Limbah Tandan Kosong Kelapa Sawit dengan Perekat Urea Formaldehida Development of Commercial Size Particleboard from Waste of Oil Palm Empty Fruit Bunches Using Urea Formaldehyde Adhesive - Bambang Subiyanto; Subyakto Subyakto; Sudijono Sudijono; Mohamad Gopar Mohamad Gopar; Entang Rasyid; Sasa Sofyan Munawar (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Development of particleboard from waste of Oil Palm empty fruit bunches (EFB) using phenol formaldehyde adhesive has been done at small size (laboratory scale) in the previous study. Further development at commercial size board is conducted in the present study. The objective of this research is to observe the effects of EFB particleboard types and density on the physical and mechanical properties of particleboard using urea formaldehyde adhesive. The types of EFB particleboard were particleboard of entirely EFB particles, board layered with sawdust and board layered with plywood.  Adhesive content used was 10% from oven dry weight of particles; wax content used was 12% from weight of adhesive. The board density was varied at 0.5 g/cm3, 0.6 g/cm3, and 0.7 g/cm3.  The EFB particles were soaked for 24 hours in cold water before used.The results showed that EFB particleboard that layered with plywood at density of 0.7 g/cm3 gave the optimum result.  Thickness swelling for all type of EFB particleboards were not met the JIS A 5908; therefore it need further study to overcome this problem. All mechanical properties such as internal bond, screw withdrawal, modulus of elasticity (MOE) and modulus of rupture (MOR) for EFB particleboard that layered with plywood were met the type 8 of JIS A 5908.